Sarcocystis neurona, Toxoplasma gondii, and Neospora caninum infection in bovine fetuses from a slaughterhouse in southern Brazil - Isac J. Roman; Larissa G. Tagarra; Fernando S. Rodrigues; Juliana F. Cargnelutti; Luis Antonio Sangioni; Fernanda S.F. Vogel (Pesquisa Veterinária Brasileira)
ABSTRACT: This study aims to describe the molecular detection of Sarcocystis neurona, Toxoplasma gondii, and Neospora caninum in brain samples obtained from bovine fetuses at a slaughterhouse in South Brazil. Brain samples from 35 fetuses of asymptomatic pregnant beef cows underwent nested polymerase chain reaction (PCR) to amplify a fragment of the 18S rRNA gene specific to S. neurona, T. gondii, and N. caninum. The amplicons were subjected to a two-step digestion process: first, with the restriction enzyme DdeI, which differentiates N. caninum from T. gondii and S. neurona; and subsequently, with the HpaII enzyme, to distinguish S. neurona from T. gondii and N. caninum. Of the 35 brain samples tested, 26 yielded positive PCR results for the 18S rRNA gene. Of these, 23 were digested with restriction enzymes, yielding 17 positive samples for S. neurona, five for N. caninum, and one for T. gondii. Specific primers for S. neurona, N. caninum, and T. gondii were employed to confirm the restriction fragment length polymorphism results. DNA sequencing and phylogenetic analysis, based on the ITS-1 region, were conducted on a positive sample for S. neurona, confirming our surprising findings. The sequence from fetus 75 exhibited a high nucleotide identity (97.79%) and clustered with S. neurona sequences available in GenBank. Molecular analyses confirmed the unprecedented detection of S. neurona, a protozoan not previously reported in cattle, in bovine fetal brain samples, thereby underscoring the necessity for further research on Apicomplexa protozoan infections in cattle.